Meningkatkan kemampuan koneksi matematik mahasiswa melalui model pembelajaran CORE - Nita Hidayati; Lessa Roesdiana (Program Studi Pendidikan Matematika, FKIP, Universitas Siliwangi, Tasikmalaya, 2019)
The issue examined in this study was about the low learning outcomes. The focus of the study discussed was the factors that influenced the learning outcomes, which was the learning model. The learning model chosen was the CORE learning model. The purpose of this study was to invetigate the problem of students' achievement of mathematical connection ability between the learning of using the CORE approach and ordinary learning. This study was a quasi-experimental study with a test design of posttest only control group design. Sampling in this study was using simple random sampling. This was done because the sample members were chosen in proportion. This research was conducted to the students of one of the universities in Karawang. The data collection method was a test, the test instrument was included a mathematical connection ability test. Indicators and variables measured in this study were the level of mathematical connection ability which included the posttest value of the mathematical connection ability test. The data were collected then analyzed using descriptive statistical analysis and inferencial statistics (t-test). Based on data analysis, the achievement of mathematical connection abilities of the students who studied using CORE learning were better than those who studied using expository learning. The achievement of students' mathematical connection skills in the class who studied using the CORE approach was categorized as high while those in the class who studied using expository learning were categorized as medium. Thus, it can be concluded that there are significant differences in student learning outcomes between the learning using CORE approach and using expository learning.